Synthesis and cytotoxic activity investigations of DNA-tropic 4-dimethylaminostyryl derivatives of N-methyl-pyrimidobenzimidazolium iodides - B. V. Paponov; A. N. Sokolova; P. S. Zdereva; S. A. Tsymbal; O. S. Shemchuk; D. N. Maystrenko; O. E. Molchanov; K. N. Semenov (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова, 2024)
Introduction. The creation of new compounds with pronounced cytotoxic activity is one of the priority goals in modern medicinal chemistry due to the emergence of multidrug resistance (MDR) to existing chemotherapy drugs for many types of tumour diseases.The objective was the synthesis of DNA-tropic heterocyclic systems containing a quaternized nitrogen atom and one or two styryl moieties as side chains. The synthesized compounds must have pronounced cytotoxic activity and moreover bind with DNA macromolecules effectively.Methods and materials. In this paper, 2 new compounds containing a 10-methyl substituted pyrimidobenzimidazolium core and 1 or 2 4-dimethylaminostyryl moieties as side chains were synthesized. The structures of targeting compounds were confirmed using mass spectrometry and NMR spectroscopy methods. The electronic spectra of these compounds were studied in this work. The investigations of targeting compounds proved their ability to bind with DNA macromolecules. The cytotoxicity of the synthesized compounds was studied on four cell lines.Results. The target compounds were obtained in four-stage synthetic procedure. The purity of the target products was confirmed using NMR spectroscopy and mass spectrometry. The synthesized compounds are effective cyanine dyes with absorption maxima in the dark red and dark violet regions of the visible spectrum for mono and bis 4-dimethylaminostyryl derivatives, respectively in the its electronic absorption spectra. Both of the synthesized compounds can form a stable complex with DNA macromolecules with a significant deepening of the colour in the solutions. The compounds showed pronounced cytotoxic activity in in vitro experiments on a number of cancer-transformed cell lines. The target compounds were shown a high cytotoxic activity against triple-negative breast cancer cells, which are extremely resistant to chemotherapy.Conclusion. 4-Dimethylaminostyryl derivatives of N-methyl-pyrimidobenzimidazolium iodides require a further study as new promising compounds with pronounced antitumor activity.